If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4(2x + -7) + 12 = 4 + 5(3x + 4) Reorder the terms: 3x + 4(-7 + 2x) + 12 = 4 + 5(3x + 4) 3x + (-7 * 4 + 2x * 4) + 12 = 4 + 5(3x + 4) 3x + (-28 + 8x) + 12 = 4 + 5(3x + 4) Reorder the terms: -28 + 12 + 3x + 8x = 4 + 5(3x + 4) Combine like terms: -28 + 12 = -16 -16 + 3x + 8x = 4 + 5(3x + 4) Combine like terms: 3x + 8x = 11x -16 + 11x = 4 + 5(3x + 4) Reorder the terms: -16 + 11x = 4 + 5(4 + 3x) -16 + 11x = 4 + (4 * 5 + 3x * 5) -16 + 11x = 4 + (20 + 15x) Combine like terms: 4 + 20 = 24 -16 + 11x = 24 + 15x Solving -16 + 11x = 24 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -16 + 11x + -15x = 24 + 15x + -15x Combine like terms: 11x + -15x = -4x -16 + -4x = 24 + 15x + -15x Combine like terms: 15x + -15x = 0 -16 + -4x = 24 + 0 -16 + -4x = 24 Add '16' to each side of the equation. -16 + 16 + -4x = 24 + 16 Combine like terms: -16 + 16 = 0 0 + -4x = 24 + 16 -4x = 24 + 16 Combine like terms: 24 + 16 = 40 -4x = 40 Divide each side by '-4'. x = -10 Simplifying x = -10
| a+39=5a-37 | | 3x^2-130x-1000=0 | | 5m+1m=100 | | 2x^3+5x-9=0 | | (x+1)(4-3i)(4+3i)=0 | | 17=-5(3+w)+w | | 3x+4(x-5)=1-5(x-3) | | 4m+1m=100 | | X^2+4x+4=289 | | 16q+17q=20 | | 10x-20x=30 | | 5x-6(7-2x)=10x | | 5x-3yx=-4+4y | | 3x-(7x-16)=-26 | | 9-21=3z | | -7x+33=6x+58 | | 4x-22+2x=180 | | Y=x^2-40 | | 2(5)+5=4(5)-5 | | 8x=41 | | 4x-22+2x= | | 7x+28=3x+4 | | 15+x=2 | | -6x+2y=15 | | 2+3(5j+2)=2(3j-6) | | 12w-16w=8 | | 4(8p+5)-4p=76 | | -6(r-1)=-(7r+8) | | .4x-.3=-0.14 | | 7c=c-6 | | c-33=8 | | -1.8+0.9+-1.4+0.4= |